2010
DOI: 10.1002/ps.1975
|View full text |Cite
|
Sign up to set email alerts
|

A new molecular method for the rapid detection of a metamitron-resistant target site in Chenopodium album

Abstract: The method allows exhaustive surveys screening C. album leaf or seed samples for the occurrence of the D1 Ser264Gly mutation to confirm or disprove metamitron resistance in the case of unsatisfactory control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 13 publications
(16 reference statements)
1
15
0
Order By: Relevance
“…The ED 50 values from the bioassay experiment indicated that the Ra and Rm populations were resistant to metamitron, as they were clearly different from the S population (Table 1). The RI for the Rm population (2.95 ± 0.60) was in accordance with the ratio 3.85 obtained by Thiel et al , who used the same population 26. The atrazine‐resistant biotype Ra had a lower RI (1.75 ± 0.39).…”
Section: Resultssupporting
confidence: 88%
“…The ED 50 values from the bioassay experiment indicated that the Ra and Rm populations were resistant to metamitron, as they were clearly different from the S population (Table 1). The RI for the Rm population (2.95 ± 0.60) was in accordance with the ratio 3.85 obtained by Thiel et al , who used the same population 26. The atrazine‐resistant biotype Ra had a lower RI (1.75 ± 0.39).…”
Section: Resultssupporting
confidence: 88%
“…and is still successfully used in screens of plastid-encoded herbicide resistance (Thiel et al, 2010). However, the approach of combining physiological characterization with local sequence analysis suffers from limitations: First, the candidate gene needs to be predictable, which implies that its biochemical and physiological attributes are already well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…(), polymorphic plants surviving herbicide treatment will probably eliminate susceptible chloroplasts and become insensitive to further herbicide treatment. Chloroplast polymorphism for the serine‐264 to glycine mutation was already confirmed in susceptible C. album ( Thiel et al ., ) and Senecio vulgaris populations (Frey et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The DNA extraction with FTA card was performed according to the protocol described by Thiel et al . (). The PCR amplification of the highly conserved psbA gene was performed using the primers psbA‐up and psbA‐low, as described in Thiel et al .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation